2009
DOI: 10.1002/wnan.40
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down particle fabrication: control of size and shape for diagnostic imaging and drug delivery

Abstract: This review discusses rational design of particles for use as therapeutic vectors and diagnostic imaging agent carriers. The emerging importance of both particle size and shape is considered, and the adaptation and modification of soft lithography methods to produce nanoparticles is highlighted. To this end, studies utilizing particles made via a process called Particle Replication In Non-wetting Templates (PRINT ™ ) are discussed. In addition, insights gained into therapeutic cargo and imaging agent delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 102 publications
(178 reference statements)
0
109
0
6
Order By: Relevance
“…We found that, as a consequence of their low modulus, these discoid microparticles bypassed several in vivo filtration mechanisms, illustrated by animal survival and dramatic increases in elimination half-lives of particles with decreasing modulus. Such deformable and long-circulating particles may find utility in the fields of drug delivery and medical imaging, where long-circulation times and varied biodistributions are often desirable characteristics (6,16,17). Further, we expect these results will stand as an introduction for particle deformability as a vital design parameter that can affect the behavior of particles on both the microand nanoscales.…”
mentioning
confidence: 91%
“…We found that, as a consequence of their low modulus, these discoid microparticles bypassed several in vivo filtration mechanisms, illustrated by animal survival and dramatic increases in elimination half-lives of particles with decreasing modulus. Such deformable and long-circulating particles may find utility in the fields of drug delivery and medical imaging, where long-circulation times and varied biodistributions are often desirable characteristics (6,16,17). Further, we expect these results will stand as an introduction for particle deformability as a vital design parameter that can affect the behavior of particles on both the microand nanoscales.…”
mentioning
confidence: 91%
“…Anisotropic polymer particles with precise shapes or heterogeneous chemistries, in particular anisotropic hydrogel particles, have demonstrated unique advantages in numerous fields. For drug delivery, tissue engineering, and diagnostic imaging, engineering nano and microparticles' shape is a way to tailor particle penetration and degradation properties 2. In the field of biosensing, unique shape and graphical patterns of particles have brought new strategies for encoding complex particle libraries for multiplex sensing applications 3.…”
mentioning
confidence: 99%
“…As a drug delivery system, the particle size is very important (25). It has been identified that particles larger than 200 nm usually are grasped by the spleen and removed by phagocytes when intravenously injected.…”
Section: Discussionmentioning
confidence: 99%